Modified positive electrode material precursor and preparation method thereof, positive electrode material, and lithium ion battery
The precursor of the cathode material is covered and modified by the Ca-doped Sr2TiMnO6 material, which solves the limitations of traditional lithium battery cathode materials in terms of energy density, cycle life and high temperature stability, and achieves significant structural stability and cyclic performance improvements.
Patent Information
- Application Number
- CN202411901727.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-04-04
AI Technical Summary
Traditional lithium battery positive electrode materials have limitations in terms of energy density, cycle life and high temperature stability, and existing coating and doping modification methods have limited performance improvements.
The cathode material precursor was coated and modified by using Ca-doped Sr2TiMnO6 material, and the Ca-doped Sr2TiMnO6 material was prepared and mixed with the cathode material precursor and sintered to obtain the modified cathode material.
It significantly improves the structural stability and circulation performance of the positive electrode material, improves the cycle life of lithium-ion batteries, and maintains good electrochemical performance.
Smart Images

Figure CN119750671A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion battery positive electrode materials, and in particular relates to a lithium ion battery precursor and a preparation method thereof, a positive electrode material and a preparation method thereof. Background Art
[0002] In the field of lithium-ion batteries, the choice of cathode materials directly determines the performance and application potential of the battery. Although traditional lithium battery cathode materials such as lithium cobalt oxide, lithium iron phosphate and ternary cathode materials have excellent electrochemical performance, they still have certain limitations in energy density, cycle life and high temperature stability. Therefore, the development of cathode materials with higher energy density and stability has become the key to improving the performance of lithium batteries.
[0003] Currently, coating and doping are the most common modification methods for positive electrode materials, among which coating modification with oxides such as CaO, SrO and TiO2 is a common modification method. However, the performance improvement of lithium battery positive electrode materials by coating with these materials is limited. Summary of the invention
[0004] In order to solve the above technical problems, the present application provides a modified positive electrode material precursor and a preparation method thereof, a modified positive electrode material, and a lithium-ion battery.
[0005] To achieve the above objectives, this application proposes the following technical solutions: In a first aspect, a modified positive electrode material precursor is provided, comprising a positive electrode material precursor and a coating coated on at least a portion of the surface of the positive electrode material precursor, wherein the coating is a Ca-doped Sr2TiMnO6 material.
[0006] In a second aspect, a method for preparing a modified positive electrode material precursor is provided, comprising: Preparation of Ca-doped Sr2TiMnO6 material; The Ca-doped Sr2TiMnO6 material is mixed with the positive electrode material precursor and sintered to obtain a modified positive electrode material precursor.
[0007] In a third aspect, a modified positive electrode material is provided, which is obtained by mixing and sintering the modified positive electrode material precursor described above or the modified positive electrode material precursor prepared by the described preparation method with a lithium source.
[0008] In a fourth aspect, a lithium-ion battery is provided, comprising the aforementioned modified positive electrode material.
[0009] Compared with the prior art, one or more of the above technical solutions can achieve at least one of the following beneficial effects: The use of Ca-modified Sr2TiMnO6 material to coat and modify the cathode material precursor can effectively optimize the interface performance of the cathode material, significantly improve the structural stability of the cathode material without significantly reducing the electrical properties of the cathode material, and thus improve the cycle life of the lithium-ion battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0011] Figure 1 The XRD diagram of the Sr2TiMnO6 powder prepared in step 1 of Example 1 and the XRD diagram of the Ca-modified Sr2TiMnO6 powder prepared in step 2. DETAILED DESCRIPTION
[0012] The present invention provides a modified positive electrode material precursor, comprising a positive electrode material precursor and a coating coated on at least a portion of the surface of the positive electrode material precursor, wherein the coating is a Ca-doped Sr2TiMnO6 material.
[0013] Sr2TiMnO6 is a composite oxide with a perovskite structure that can provide excellent ionic and electronic conductivity in electrochemical applications. Compared with simple manganese oxide (MnO2) and titanium oxide (TiO2), Sr2TiMnO6 has better structural stability and ion migration ability, and can maintain good chemical and thermal stability at high temperatures, thereby improving the material's life and performance in battery charge and discharge cycles. 2+ Ion doping can effectively reduce the lattice constant of Sr2TiMnO6, promote the compression of the crystal structure, and improve the electronic conductivity and ion diffusion. Ca-doped Sr2TiMnO6 can coat the cathode material precursor, which can provide better ion mobility and more stable electrochemical performance while maintaining the good conductivity of the cathode material. On the other hand, it can optimize the interface performance of the cathode material and enhance the corrosion resistance of the material, thus significantly improving its cycle performance without significantly reducing the discharge capacity of the cathode material.
[0014] In some preferred embodiments, the coating is 0.005~0.05:1 of the mass of the positive electrode material precursor, for example 0.005:1, 0.01:1, 0.012:1, 0.015:1, 0.018:1, 0.02:1, 0.022:1, 0.025:1, 0.028:1, 0.03:1, 0.032:1, 0.035:1, 0.038:1, 0.04:1, 0.042:1, 0.045:1, 0.048:1, 0.05:1, etc.
[0015] In some preferred embodiments, in the coating, the molar amount of Ca is 0.25-2.5% of the molar amount of Sr, for example, 0.25%, 0.5%, 1%, 1.2%, 1.5%, 1.8%, 2%, 2.2%, 2.5%, etc.
[0016] In some preferred embodiments, the positive electrode material precursor is nickel cobalt manganese hydroxide.
[0017] In some preferred embodiments, the chemical formula of the nickel-cobalt-manganese hydroxide is Ni x Co y Mn z (OH)2, where 0.7≤x<1, 0≤y≤0.2, 0<z≤0.3, x+y+z =1.
[0018] The present invention provides a method for preparing a modified positive electrode material precursor, comprising: Preparation of Ca-doped Sr2TiMnO6 material; The Ca-doped Sr2TiMnO6 material is mixed with the positive electrode material precursor and sintered to obtain a modified positive electrode material precursor.
[0019] In some preferred embodiments, the sintering temperature is 200-400°C, for example, 200°C, 250°C, 300°C, 350°C, 400°C, etc.; the sintering time is 1-6h, for example, 1h, 2h, 3h, 4h, 5h, 6h, etc.
[0020] In some preferred embodiments, the preparation of Ca-doped Sr2TiMnO6 material includes: dissolving a soluble calcium source in water to obtain solution A, adding Sr2TiMnO6 material to solution A, stirring evenly, heating and stirring until the solvent is evaporated to dryness to obtain a solid, and calcining the solid to obtain Ca-doped Sr2TiMnO6 material.
[0021] In some preferred embodiments, the calcination temperature is 900-1200°C, for example, 900°C, 950°C, 1000°C, 1050°C, 1100°C, 1150°C, 1200°C, etc.; the calcination time is 3-12h, for example, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, etc.; the calcination atmosphere is argon atmosphere.
[0022] In some embodiments, the soluble calcium source is one or two of calcium nitrate, calcium acetate, and calcium chloride.
[0023] In some embodiments, the Sr2TiMnO6 material is prepared by solid phase sintering, specifically, comprising: mixing a strontium source, a manganese source and a titanium source, and then solid phase sintering them under an inert atmosphere. The strontium source, the manganese source and the titanium source can be conventional compounds in the art, such as oxides, nitrates, oxalates, carbonates, etc. The temperature of the solid phase sintering can also be conventional temperatures in the art, such as 900~1200°C, such as 900°C, 950°C, 1000°C, 1050°C, 1100°C, 1150°C, 1200°C, etc.; the solid phase sintering time is 2~12h, such as 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, etc. The mixing can be ball milling.
[0024] When nickel-cobalt-manganese hydroxide is used as the positive electrode material precursor, the positive electrode material precursor can be prepared by a conventional coprecipitation method or can be commercially available.
[0025] The present invention also provides a modified positive electrode material, which is obtained by mixing and sintering the modified positive electrode material precursor or the modified positive electrode material precursor prepared by the aforementioned preparation method with a lithium source.
[0026] The ratio of the lithium source to the modified positive electrode material precursor is a conventional ratio in the art, for example, the molar ratio of lithium in the lithium source to the modified positive electrode material precursor is 1-1.1:1.
[0027] The lithium source may be a conventional lithium source in the art, such as lithium hydroxide, lithium carbonate, lithium oxide, lithium acetate, lithium oxalate, and the like.
[0028] The sintering temperature may be a conventional sintering temperature in the art, such as 750-950°C.
[0029] The present invention also provides a lithium ion battery, comprising the aforementioned modified positive electrode material.
[0030] In order to facilitate the understanding of the present invention, the present invention will be described in more comprehensive and detailed manner below in conjunction with the accompanying drawings and preferred embodiments of the specification, but the protection scope of the present invention is not limited to the following specific embodiments.
[0031] Example 1 Step S1, preparation of Sr2TiMnO6: First, weigh 4.114 g of strontium acetate, 0.798 g of TiO2 and 0.869 g of MnO2 in a molar ratio of 2:1:1, add the raw materials into a ball mill, add 30 mL of anhydrous ethanol as a medium, and ball mill at 300 rpm for 5 hours to ensure sufficient mixing. After the ball milling is completed, the mixture is dried at 80°C for 12 hours to remove the ethanol. The dried mixture is then placed in a muffle furnace and calcined at 1300°C for 12 hours under argon protection. After completion, it is naturally cooled to room temperature. After cooling, the calcined product is crushed to obtain a uniform Sr2TiMnO6 powder, whose XRD pattern is shown as follows Figure 1 shown.
[0032] Step S2, preparation of Ca-doped Sr2TiMnO6: Weigh Ca(NO3)2·4H2O and dissolve it in 20mL deionized water to prepare a solution containing 0.2mmol of calcium. Add 0.02mol of Sr2TiMnO6 powder to the calcium solution, stir at room temperature for a period of time, heat and stir the mixed solution at 80°C until the water is evaporated to obtain a solid, dry the solid to remove moisture, and then calcine the dried mixture at 900°C for 8 hours under argon protection. After the calcination, cool it to room temperature and crush the product to obtain Ca-doped modified Sr2TiMnO6 powder, whose XRD pattern is as shown below: Figure 1 As shown, no obvious impurities were observed.
[0033] Step S3, preparation of ternary precursor: prepare sulfates of nickel, cobalt and manganese, prepare a mixed sulfate solution in a molar ratio of 9:0.3:0.7, use NaOH solution as a precipitant, conduct a coprecipitation reaction, the reaction temperature is 60°C, the reaction time is 20 hours, and the pH value is controlled to be 10 during the reaction process to obtain a coprecipitation slurry. The obtained slurry is filtered, washed with deionized water 3 times, and dried at 120°C for 12 hours to obtain a ternary precursor powder.
[0034] Step S4: Ca-doped Sr2TiMnO6 coated precursor Ca-doped Sr2TiMnO6 powder and ternary precursor Ni 0.9 Co 0.03 Mn 0.07 (OH)2 was mixed in a mass ratio of 0.01:1 and pretreated at 250°C for 4 hours to promote the bonding of the composite and the precursor. After sintering, the composite was cooled to room temperature to obtain a composite-coated precursor.
[0035] Step S5: Preparation of positive electrode material from the modified precursor The modified precursor was mixed with lithium salt at a molar ratio of precursor to Li of 1:1.05, and sintered at 850° C. in an air atmosphere for 22 hours to obtain the corresponding coated modified positive electrode material.
[0036] Comparative Example 1 Step S1, preparation of Sr2TiMnO6: First, weigh 4.114 g of strontium acetate, 0.798 g of TiO2 and 0.869 g of MnO2 according to a molar ratio of 2:1:1, add the raw materials into a ball mill, add 30 mL of anhydrous ethanol as a medium, and ball mill at 300 rpm for 5 hours to ensure sufficient mixing. After the ball milling is completed, the mixture is dried at 80°C for 12 hours to remove the ethanol. The dried mixture is then placed in a muffle furnace and calcined at 1300°C for 12 hours under argon protection, and then naturally cooled to room temperature. After the calcined product is cooled, it is crushed to obtain a uniform Sr2TiMnO6 powder.
[0037] Step S2, preparation of ternary precursor: prepare sulfates of nickel, cobalt and manganese, prepare a mixed sulfate solution in a molar ratio of 9:0.3:0.7, use NaOH solution as a precipitant, conduct a coprecipitation reaction, the reaction temperature is 60°C, the reaction time is 6 hours, and the pH value is controlled to be 10 during the reaction process to obtain a coprecipitation slurry. The obtained slurry is filtered, washed with deionized water 3 times, and dried at 120°C for 12 hours to obtain a ternary precursor powder.
[0038] Step S3: Sr2TiMnO6 coated precursor Sr2TiMnO6 powder and ternary precursor Ni 0.9 Co 0.03 Mn 0.07 (OH)2 was mixed in a mass ratio of 0.01:1 and pretreated at 250°C for 4 hours to promote the bonding of Sr2TiMnO6 with the precursor. After sintering, it was cooled to room temperature to obtain a Sr2TiMnO6-coated precursor.
[0039] Step S4: Preparation of positive electrode material from modified precursor The modified precursor was added with lithium salt in a molar ratio of precursor to lithium of 1:1.05, and the mixture was sintered at 850° C. in an air atmosphere for 22 hours to obtain a coated modified positive electrode material.
[0040] Comparative Example 2 Step S1, preparation of ternary precursor: prepare sulfates of nickel, cobalt and manganese, prepare a mixed sulfate solution in a molar ratio of 9:0.3:0.7, use NaOH solution as a precipitant, conduct a coprecipitation reaction, the reaction temperature is 60°C, the reaction time is 20 hours, and the pH value is controlled to be 10 during the reaction process to obtain a coprecipitation slurry. The obtained slurry is filtered, washed with deionized water 3 times, and dried at 120°C for 12 hours to obtain a ternary precursor powder.
[0041] Step S2: Preparation of positive electrode material from unmodified precursor: 0.9 Co 0.03 Mn 0.07 (OH)2 and lithium salt are mixed in a molar ratio of precursor to lithium of 1:1.05, and sintered at 850°C in an air atmosphere for 22 hours to obtain the corresponding positive electrode material.
[0042] Example 2 Step S1, preparation of Sr2TiMnO6: First, weigh 4.114 g of strontium acetate, 0.798 g of TiO2 and 0.869 g of MnO2 in a molar ratio of 2:1:1, add the raw materials into a ball mill, add 30 mL of anhydrous ethanol as a medium, and ball mill at 300 rpm for 5 hours to ensure sufficient mixing. After the ball milling is completed, the mixture is dried at 80°C for 12 hours to remove the ethanol. The dried mixture is then placed in a muffle furnace and calcined at 1300°C for 12 hours under argon protection. After completion, it is naturally cooled to room temperature. After cooling, the calcined product is crushed to obtain a uniform Sr2TiMnO6 powder, whose XRD pattern is shown as follows Figure 1 shown.
[0043] Step S2, preparation of Ca-doped Sr2TiMnO6: Weigh Ca(NO3)2·4H2O and dissolve it in 20mL deionized water to prepare a solution containing 0.4mmol of calcium. Add 0.02mol of Sr2TiMnO6 powder to the calcium solution, stir at room temperature for a period of time, heat and stir the mixed solution at 80°C until the water is evaporated to obtain a solid, dry the solid to remove moisture, and then calcine the dried mixture at 850°C for 8 hours under argon protection. After the calcination, cool it to room temperature and crush the product to obtain Ca-doped modified Sr2TiMnO6 powder, whose XRD pattern is shown as follows Figure 1 As shown, no obvious impurities were observed.
[0044] Step S3, preparation of ternary precursor: prepare sulfates of nickel, cobalt and manganese, prepare a mixed sulfate solution in a molar ratio of 9:0.3:0.7, use NaOH solution as a precipitant, conduct a coprecipitation reaction, the reaction temperature is 60°C, the reaction time is 20 hours, and the pH value is controlled to be 10 during the reaction process to obtain a coprecipitation slurry. The obtained slurry is filtered, washed with deionized water 3 times, and dried at 120°C for 12 hours to obtain a ternary precursor powder.
[0045] Step S4: Ca-doped Sr2TiMnO6 coated precursor Ca-doped Sr2TiMnO6 powder and ternary precursor Ni 0.9 Co 0.03 Mn 0.07 (OH)2 was mixed in a mass ratio of 0.005:1 and pretreated at 300°C for 4 hours to promote the bonding of the composite and the precursor. After sintering, the composite was cooled to room temperature to obtain a composite-coated precursor.
[0046] Step S5: Preparation of positive electrode material from the modified precursor The modified precursor was mixed with lithium salt at a molar ratio of precursor to Li of 1:1.05, and sintered at 850° C. in an air atmosphere for 22 hours to obtain the corresponding coated modified positive electrode material.
[0047] Example 3 Step S1, preparation of Sr2TiMnO6: First, weigh 4.114 g of strontium acetate, 0.798 g of TiO2 and 0.869 g of MnO2 in a molar ratio of 2:1:1, add the raw materials into a ball mill, add 30 mL of anhydrous ethanol as a medium, and ball mill at 300 rpm for 5 hours to ensure sufficient mixing. After the ball milling is completed, the mixture is dried at 80°C for 12 hours to remove the ethanol. The dried mixture is then placed in a muffle furnace and calcined at 1300°C for 12 hours under argon protection. After completion, it is naturally cooled to room temperature. After cooling, the calcined product is crushed to obtain a uniform Sr2TiMnO6 powder, whose XRD pattern is shown as follows Figure 1 shown.
[0048] Step S2, preparation of Ca-doped Sr2TiMnO6: Weigh Ca(NO3)2·4H2O and dissolve it in 20mL deionized water to prepare a solution containing 0.6mmol of calcium. Add 0.02mol of Sr2TiMnO6 powder to the calcium solution, stir at room temperature for a period of time, heat and stir the mixed solution at 80°C until the water is evaporated to obtain a solid, dry the solid to remove moisture, and then calcine the dried mixture at 1000°C for 6 hours under argon protection. After the calcination, cool it to room temperature and crush the product to obtain Ca-doped modified Sr2TiMnO6 powder, whose XRD pattern is as shown below: Figure 1 As shown, no obvious impurities were observed.
[0049] Step S3, preparation of ternary precursor: prepare sulfates of nickel, cobalt and manganese, prepare a mixed sulfate solution in a molar ratio of 9:0.3:0.7, use NaOH solution as a precipitant, conduct a coprecipitation reaction, the reaction temperature is 60°C, the reaction time is 20 hours, and the pH value is controlled to be 10 during the reaction process to obtain a coprecipitation slurry. The obtained slurry is filtered, washed with deionized water 3 times, and dried at 120°C for 12 hours to obtain a ternary precursor powder.
[0050] Step S4: Ca-doped Sr2TiMnO6 coated precursor Ca-doped Sr2TiMnO6 powder and ternary precursor Ni 0.9 Co 0.03 Mn 0.07 (OH)2 was mixed in a mass ratio of 0.012:1 and pretreated at 350°C for 3 hours to promote the bonding of the composite and the precursor. After sintering, the composite was cooled to room temperature to obtain a composite-coated precursor.
[0051] Step S5: Preparation of positive electrode material from the modified precursor The modified precursor was mixed with lithium salt at a molar ratio of precursor to Li of 1:1.05, and sintered at 850° C. in an air atmosphere for 22 hours to obtain the corresponding coated modified positive electrode material.
[0052] The positive electrode materials of Examples 1 to 3 and Comparative Examples 1 to 2 were respectively assembled into batteries in the following manner: the positive electrode material, the binder PVDF, and the conductive agent were mixed in a mass ratio of 8:1:1, dry-ground for 10 minutes, an appropriate amount of solvent NMP was added, and the positive electrode slurry was obtained after being stirred evenly using a homogenizer. The positive electrode slurry was evenly coated on an aluminum foil and dried overnight in an oven at 100°C to ensure that the coating was dry. The positive electrode sheet was then cut into button battery discs (12 mm in diameter) of suitable size; a metal lithium sheet was used as a negative electrode; LB-037 (1M LiPF6in DEC:EC:EMC=1:1:1 Vol%) was used as an electrolyte, 70 μL was added dropwise, and Celgard2325 was used as a separator to assemble a button battery.
[0053] The electrical properties of the assembled batteries were tested in the following manner: the test temperature was 25°C, the operating voltage range was 3.0~4.3 V, and they were cycled for 2 cycles at 0.1C, and then cycled for 100 cycles at 0.5C, 1C, and 2C respectively.
[0054] As can be seen from Table 1, compared with the battery assembled with the positive electrode material prepared by the unmodified precursor in Comparative Example 2, the battery assembled with the positive electrode material prepared by the Sr2TiMnO6 coated modified precursor in Comparative Example 1 has significantly improved cycle performance at low rates and high rates, and the electrical performance is reduced; the batteries assembled with the positive electrode material prepared by the Ca-doped Sr2TiMnO6 coated modified precursor in Examples 1 to 3 have further improved cycle performance at low rates and high rates compared with the batteries assembled with the positive electrode material prepared in Comparative Example 1, and the discharge specific capacity and rate performance are also improved. Compared with the battery assembled with the positive electrode material prepared by the unmodified precursor in Comparative Example 2, the first discharge specific capacity of the battery assembled with the positive electrode material is only slightly reduced, but the cycle performance at high rates and low rates is significantly improved.
[0055] Table 1 The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A modified cathode material precursor, characterized in that: It comprises a positive electrode material precursor and a coating coated on at least a part of the surface of the positive electrode material precursor, wherein the coating is a Ca-doped Sr2TiMnO6 material.
2. The modified positive electrode material precursor according to claim 1, characterized in that: The coating is 0.005~0.05:1 of the mass of the positive electrode material precursor; In the coating, the molar amount of Ca is 0.25-2.5% of the molar amount of Sr.
3. The modified positive electrode material precursor according to claim 1 or 2, characterized in that: The positive electrode material precursor is nickel cobalt manganese hydroxide; The chemical formula of the nickel-cobalt-manganese hydroxide is Ni x Co y Mn z (OH)2, where 0.7≤x<1, 0≤y≤0.2, 0<z≤0.3, x+y+z =1.
4. The method for preparing a modified positive electrode material precursor according to any one of claims 1 to 3, characterized in that: include: Preparation of Ca-doped Sr2TiMnO6 material; The Ca-doped Sr2TiMnO6 material is mixed with the positive electrode material precursor and sintered to obtain a modified positive electrode material precursor.
5. The method for preparing a modified positive electrode material precursor according to claim 4, characterized in that: The sintering temperature is 200-400° C., and the sintering time is 1-6 hours.
6. The method for preparing a modified positive electrode material precursor according to claim 4, characterized in that: The preparation of the Ca-doped Sr2TiMnO6 material includes: dissolving a soluble calcium source in water to obtain a solution A, adding the Sr2TiMnO6 material to the solution A, stirring evenly, heating and stirring until the solvent is evaporated to dryness to obtain a solid, and calcining the solid to obtain the Ca-doped Sr2TiMnO6 material.
7. The method for preparing a modified positive electrode material precursor according to claim 6, characterized in that: The calcination temperature is 900-1200° C.; the calcination time is 3-12 hours; and the calcination atmosphere is an argon atmosphere.
8. The method for preparing a modified positive electrode material precursor according to claim 6, characterized in that: The soluble calcium source is one or both of calcium nitrate and calcium acetate.
9. A modified positive electrode material, characterized in that: The modified positive electrode material precursor according to any one of claims 1 to 3 or the modified positive electrode material precursor prepared by the preparation method according to any one of claims 4 to 8 is mixed with a lithium source and sintered.
10. A lithium ion battery, characterized in that Comprising the modified positive electrode material as claimed in claim 9.